The use of supplementary materials in EFL classes: A comparative analysis of public and private high schools. - Matute Macías, Pastora del Carmen (2012)
This study is titled “The use of supplementary materials in EFL: A comparative Analysis of Public and Private High Schools”. It was carried out to determine how Ecuadorian teachers use instructional materials in private and public high schools. Two high schools located to the north of Guayaquil were selected to conduct this research. The participants were English teachers from 1st, 2nd, and 3rd senior year; a student from each course also participated in this investigation. This study was done using a qualitative and quantitative approach. Five classes were observed in each course and the gathered information was analyzed, described, and compared. In addition, teachers were interviewed using a questionnaire to know their opinion of the importance of supplementary materials and students’ learning styles. A survey was used also to gather students’ opinion of the materials used in each observed class. Once all information was analyzed and compared, conclusions revealed that the blackboard was the only supplementary material used in the public high school, while in the private high school the more frequently materials used were the whiteboard and digital board.